Enantioselective Organocatalytic Addition of Nitromethane to Trifluoromethyl Aryl Ketimines Promoted by Electron‐Rich Bifunctional Iminophosphoranes. Issue 7 (30th March 2023) - Krstić, Milena; Benaglia, Maurizio; Gazzotti, Margherita; Colombo, Eleonora; Sanz, Miguel
Abstract: Thiourea‐based iminophosphorane (BIMP) organocatalysts featuring SPhos‐ or BIDIME phosphine units have been developed and successfully applied in the asymmetric addition of nitromethane to N ‐Boc‐protected trifluoromethyl aryl ketimines. α‐Trifluoromethyl β‐nitroamines were obtained in 40–82% isolated yields and 80–95% enantioselectivities. A careful evaluation of the catalytic activity of BIMPs indicates that the catalysts derived from the combination via Staudinger reaction of a chiral 1, 2‐amino alcohol‐derived thiourea‐organoazide with electron‐rich phosphines, promote the aza‐Henry reaction on fluorinated ketimines with the highest enantioselectivity, leading to the amine featuring a tetrasubstituted stereocenter in up to 95% ee. The reaction was performed also on gram scale, without loss of enantioselectivity. Abstract :